HUBUNGAN AGAMA DAN NEGARA DI INDONESIA - Dahlan, Moh (Analisis: Jurnal Studi Keislaman, 2014)
RELIGION  AND  STATE  RELATIONS  IN  INDONESIA:  The relationship   between   religion  and  the  state   has  become  the actual  and dynamic discourse in every phase of the civilization development, both in the West and the East. The discourse mainly focuses on the form of the state  whether  integral,  symbiotic  or secular.  Departing  from the  discourse,  this  study  examines  the relationship  between religion (Islam) and the state  in Indonesia. The approach used is Martin Heidegger’s hermeneutics, while the assessment method used is the comparative method. The results of this study indicate that the Prophet, historically and normatively, had formulated  the Medina State  based on the Medina Charter which its spirit was  based on the Qur’an, not based on the Quran literally. By the same line, the Muslim scholars who became the founder of the Indonesian State had also formulated Pancasila- as it was set forth in the Preamble of the NKRI’s 1945 Constitution – as an ideal foundation in establishing the dynamic and dialectical relationship between religion and state in Indonesia. The substance of religious norms was applied after the promulgation  of, and in accordance  with,  Pancasila  and the  NKRI’s  1945 Constitution. The relationship between religion and the state, therefore, can be built based on the symbiotic or dynamic-dialectical typology.